Growth Potential and Yield of Five Varieties of Glutinous Rice (Oryza sativa glutinosa) In Three Types of Soil - Lu'luil Maknun; Sunawan Sunawan; Abdul Basit (AGRONISMA, 2021)
The condition of agricultural land in Indonesia in general has greatly decreased productivity. This is due to soil fertility degradation due to agricultural intensification. In addition, with the transfer of land functions due to the needs of residential residents, especially in the city, which uses productive rice fields as housing, this results in a considerable narrowing of the land every year. Each type of soil has a different nutrient content, Therefore it is necessary to identify the type of soil. The purpose of this study is to find out the growth potential and yield of several types of glutinous rice (Oryza sativa glutinos) on three types of soil (Inceptisol soil, Entisol soil and Andisol soil). The research was conducted at the Green House faculty of agriculture, Islamic University of Malang in October 2020 until April 2021. The method used in this study is Split Plot Design which is prepared with Randomized Design Group of 2 factors: The first factor is soil type (J) consists of: J1 = Inceptisol, J2= Entisol, J3= Andisol. The second factor is the variety of plants (V) there are 5 types of varieties, namely: V1 = Varieties Wagamba (Black) Ambon, V2 = Local Varieties Bondowoso 3 (White), V3 = Varieties Wangkaluku (Red), V4 = Varieties Payaman 20 (White), V5 = Local Varieties bondowoso 1 (Black). The results showed that local varieties bondosowoso 1 (V5) and soil Andisol (J3) are able to provide the best growth response to soil type treatment and variety treatment. Payaman 20 (V4) and Andisol soil (J3) varieties are able to provide the best result response to the treatment of soil types and varieties.